2015
DOI: 10.14334/jitv.v20i3.1186
|View full text |Cite
|
Sign up to set email alerts
|

Administration of extract Salix tetrasperma combined with extract of turmeric and neem to improve eggs quality of chicken reared under heat stress

Abstract: ABSTRAKSugito, Hambal M, Isa M, Nurliana, Delima M. 2015. Pemberian ekstrak Salix tertrasperma kombinasi dengan ekstrak kunyit dan mimba untuk peningkatan kualitas telur ayam yang dipelihara pada suasana stres panas. JITV 20(3): [193][194][195][196][197][198][199]. DOI: http://dx.doi.org/10. 14334/jitv.v20i3.1186 Kualitas telur akan menurun apabila ayam mengalami stres panas. Pemberian beberapa jenis ekstrak tanaman dilaporkan dapat mengurangi dampak tersebut. Tujuan penelitian ini adalah untuk mengetahui e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…Giving salix extract to chickens that are experiencing and not experiencing heat stress did not affected the carcass weight. This result is different from previous studies that Salix extract can inhibit the body weight reduction of heat stressed chickens [5]. The difference of the results can caused by the his differences in chicken age, and days or time of administration of salix extract.…”
Section: Carcass Weightcontrasting
confidence: 99%
See 1 more Smart Citation
“…Giving salix extract to chickens that are experiencing and not experiencing heat stress did not affected the carcass weight. This result is different from previous studies that Salix extract can inhibit the body weight reduction of heat stressed chickens [5]. The difference of the results can caused by the his differences in chicken age, and days or time of administration of salix extract.…”
Section: Carcass Weightcontrasting
confidence: 99%
“…Some researchers reported that administration of plant extracts can significantly improve the negative effects of heat stress on broiler chickens [3,4]. The application of salix (Salix tetrasperma Roxb) leaf extract to chickens can reduce the negative effects of heat stress [5]. Salix plant extracts can also reduce cholesterol in meat [6].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have proven that giving Salix tetrasperma Roxb. extract to broilers is able to improve some of the negative effects of heat stress [23][24][25][26][27]. e improvement in this condition was due to the work activity of bioactive compounds contained in the Salix plant extract, which stimulated the activity of several biochemical compounds in the chicken body to reduce the negative effects of heat stress.…”
Section: Introductionmentioning
confidence: 99%